VENTRICULAR SEPTAL DEFECT: CASE REPORTINA DOG - Dávila F., Roberto (2014)
The ventricular septal defect is an anomaly linked to genetics in some dog breeds,where an abnormal communication between the ventricles is kept allowing blood flowbetween ventricles. The magnitude and direction of communication depend on the sizeof the hole and the relative resistances in the pulmonary and systemic circulations. Thereport describes a clinical case of a male Fox Terrier, 20 months old that showed cyanoticmucous membranes and abnormal heart sound on auscultation. The echocardiographyrevealed a ventricular septal defect and hypertrophy of both ventricles.